Application of Biofertilizer Combined with Bioactivator in the Vegetative Phase of Inpari 32 Rice Variety - Mohammad Ali Mudhor; Ari Istanti; Mokhtar Effendi; Vad’aq Babgei Nur Muhammad; As’ad Surya Akbar; Sukma Septia Ayu; Shabrina Amalia Islami (Journal of Applied Agricultural Science and Technology, 2026)
Sustainable rice cultivation requires effective nutrient management strategies to reduce chemical fertilizer dependency. Biofertilizers enriched with humic acid and microbial consortia offer an eco-friendly alternative to enhance soil fertility and plant productivity. This study evaluated the effects of biofertilizer combined with humic acid and a microbial consortium on vegetative growth, chlorophyll content, and macronutrient availability in Inpari 32 rice. The experiment was conducted in a greenhouse at Banyuwangi State Polytechnic using a completely randomized factorial design with two biofertilizer types: biofertilizer + humic acid (B1) and biofertilizer + microbial consortium (Bacillus, Trichoderma, Saccharomyces) (B2), and three application doses: 300 g, 400 g, and 500 g per pot. Although ANOVA results indicated no statistically significant differences among treatments, a consistent positive trend was observed in plant height, tiller number, and chlorophyll content at the 400 g dose. Soil N, P, and K levels tended to decrease, possibly due to enhanced nutrient uptake by plants, suggesting an improved nutrient use efficiency. Overall, the combination of biofertilizer and humic acid at the 400 g dose tended to show higher values compared to other treatments, although these differences were not statistically significant. These findings support the use of multi-species microbial biofertilizers and IoT-based precision fertilization systems to promote sustainable rice production in Indonesia.